New Onset of Symptomatic Peptic Ulcer Disease Postpartum Secondary to Nonsteroidal Anti-Inflammatory Drug Use - Maggie Tallmadge; Margaret MacBeth; Anna Palatnik (Case Reports in Obstetrics and Gynecology)
The use of nonsteroidal anti-inflammatory drug (NSAID) medications is a risk factor for peptic ulcer disease (PUD). PUD in the postpartum period is rare, despite the common use of NSAIDs. A G1P0 presented 6 days postcesarean section with fatigue, lightheadedness, melenic stools, and a hemoglobin of 5.4 g/dL after using NSAIDs and acetaminophen for postoperative pain control. An esophagogastroduodenoscopy (EGD) was performed for a suspected upper gastrointestinal bleed and found one gastric and one duodenal ulcer. Though typically used for a short course in the postpartum period, NSAIDs remain a predisposing risk factor for PUD postpartum, and patients and providers must be aware of this risk.